Guía para la identificación de las áreas sembradas en palma de aceite, a partir del uso de la plataforma de Google Earth Engine (Estudio de caso: municipio de Maní – Casanare) (2023)
This document provides a comprehensive overview of the JavaScript code used within the Google Earth Engine (GEE) platform and serves as a Methodological Guide for the Identification of Oil Palm cultivation areas using supervised classification methods with Random Forest. The guide outlines detailed step-by-step procedures and recommends specific functions. Furthermore, the source code is made available to the public, simplifying access and enabling reproduction by other users of Geographic Information Systems (GIS).